IMPROVING EFFECTIVENESS AND EFFICIENCY OF TAX OBJECTION PROCESS: LESSON LEARNED FROM JAPAN - Galih Ardin (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2023)
The Directorate General of Taxes (DGT) reports that the number of tax objections and non-objection cases has increased significantly during the COVID-19 pandemic in 2020. This number is the highest in DGT’s history. Nevertheless, the number of tax appeals earned by DGT was constantly under 50%. This fact sufficiently describes the ineffectiveness and inefficiency of tax objection processes. This study aims to explore the factors causing ineffectiveness and inefficiency of tax objection process in Indonesia and to seek alternative solutions for improvement. This research employed a qualitative method through literature study and comparative study with Japan. The reason of choosing Japan as country of comparison because this country experienced the same condition in 1970. This study found that the ineffectiveness and inefficiency of the objection process occur due to the tendency of the objection process to take side with the government. In other words, the objection process is not independent from the taxpayer's perspective. To overcome this problem, the government should establish an independent agency separated from the tax disposition authority.